A novel nitrogen-containing DPO derivative as flame retardant and co-curing agent for epoxy resin. (9th February 2022) - Mei, Fengce; Tian, Chong; Li, Hubo; Huang, Shan; Yu, Qing; Han, Yuxi; Wang, Zhongwei
Abstract: A phosphorous-nitrogen flame retardant 1-N, 4-N-bis(diphenylphosphorylmethyl)benzene-1, 4-diamine (DPO-N) was synthesized by the reaction of p -phenylenediamine, formaldehyde and diphenylphosphine oxide (DPO). The modified epoxy resin (EP) was prepared using DPO-N as a flame retardant and co-curing agent in the presence of 4, 4'-diaminodiphenylsulfone to cure bisphenol A diglycidyl ether (DGEBA). The flame retardancy of the DPO-N-modified EP was evaluated by the limiting oxygen index (LOI), vertical burning test (UL-94) and cone calorimeter test. The results showed that the EP/DPO-N-0.7 (DPO-N-modified EP at a phosphorus content of 0.7 wt.%) passed the UL-94 V-0 rating test, and the LOI value of the sample increased to 30.4%. The peak of the heat release rate (pk-HRR), average of the heat release rate (av-HRR) and average of the effective heat of combustion (av-EHC) of the modified EPs were reduced by 32.4, 27.4 and 28.4%, respectively. The flame retardant mechanism was investigated by scanning electron microscopy, pyrolysis/gas chromatography-mass spectrometry and Fourier transform infrared spectroscopy analyses. The results demonstrated that DPO-N exerted its flame-retardant effect through the barrier effect of the condensed phase and the quenching effect of the gas phase. Furthermore, the water resistance of the EP was enhanced with the incorporation of DPO-N. Graphical Abstract: UF0001